2019
DOI: 10.7150/ijms.36131
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin Promoter Methylation Altered in Major Depressive Disorder

Abstract: Aims: To determine the extent of DNA methylation of parvalbumin gene (PVALB) promoter in major depressive disorder (MDD) patients with and without suicide attempt in comparison with healthy controls.Methods: The extracted DNA from dried blood spots of MDD patients (n = 92) including non-suicidal MDD and suicidal-MDD subgroups (n = 45 and n = 47, respectively) and age-matched control subjects (n = 95) was used for DNA methylation analysis at four CpG sites in the promoter sequence of PVALB by pyrosequencing.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…CpG site 40 showed higher methylation levels (>15%), though there were no significant effects observed from our manipulations on methylation percentage at this site. These findings are inconsistent with past findings of hypermethylation of CpG site 40 for both MDD patients (Thaweethee-Sukjai et al, 2019) and schizophrenia rodent models (Fachim et al, 2016). However, the fact that there was a lot of variability in samples and many samples that showed no methylation, this may obscure subtle effects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…CpG site 40 showed higher methylation levels (>15%), though there were no significant effects observed from our manipulations on methylation percentage at this site. These findings are inconsistent with past findings of hypermethylation of CpG site 40 for both MDD patients (Thaweethee-Sukjai et al, 2019) and schizophrenia rodent models (Fachim et al, 2016). However, the fact that there was a lot of variability in samples and many samples that showed no methylation, this may obscure subtle effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with schizophrenia show reduced PFC density of PV-containing interneurons (Kaar et al, 2019). Additionally, in humans with schizophrenia or major depressive disorder, and in mouse models of schizophrenia, hypermethylation of the Pvalb promoter is associated with decreased PV protein (Fachim et al, 2018; Thaweethee-Sukjai et al, 2019). Changes in PV protein output in response to methylation suggest that the Pvalb promoter region is sensitive to methylation, and that methylation impacts the transcriptional profile of PV.…”
Section: Introductionmentioning
confidence: 99%
“…One widely observed neural change involves alterations in overall inhibitory/GABAergic function (Page and Coutellier, 2019 ; Prévot and Sibille, 2021 ), which are likely exacerbated by adverse experiences (Maguire, 2014 ). Parvalbumin (PV), a calcium-binding protein expressed within a specific subset of GABAergic neurons, is thought to be involved in affective dysregulation characteristic of anxiety (e.g., Page et al, 2019 ; Xiao et al, 2020 ) and depression (e.g., Perova et al, 2015 ; Thaweethee-Sukjai et al, 2019 ). Indeed, reduced PV levels are associated with increased anxiety-like behavior and affective dysfunction in rodent studies (Godavarthi et al, 2014 ; Lussier and Stevens, 2016 ; Xu et al, 2016 ; Todorović et al, 2019 ; Vojtechova et al, 2021 ) and indirectly in human studies looking at Tourette syndrome, which is thought to be closely related to anxiety (Kalanithi et al, 2005 ; Kataoka et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective analysis of major depressive disorder in adolescent girls, the authors found that all four significant CpGs in NR3C1 were in the gene body region: Two sites were located within a transcription factor-binding site (TFBS) region, one was in a region of open chromatin, and one site associated with an enhancer element [ 47 ]. Benjamard et al [ 48 ] reported that in the promoter region of parvalbumin, methylation was significantly increased at CpG2 and decreased at CpG4 in the MDD group compared to the control group. Some alterations of CpGs are limited to specific gene phenotypes.…”
Section: Discussionmentioning
confidence: 99%